Pendampingan Fikih Perempuan bagi Remaja Muslimah Migran Indonesia untuk Meluruskan Miskonsepsi Tentang Haid, Istihadhah dan Fasad. - Dwi Apriliana; Ahmad Ihwanul Muttaqin; Muhammad Tohir Haqiqi; Sarah Lady Diana Islamy; Achmad Choiruddin (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Education is an essential means of improving knowledge and the quality of life of communities, including Indonesian migrant students in Malaysia who face various limitations in accessing education. One of the problems identified at Sanggar Bimbingan Sungai Mulia 5 (SBSM) in Kuala Lumpur is the low level of understanding among Muslim adolescent girls regarding women’s jurisprudence (fiqh), particularly concerning menstruation (hayd), irregular bleeding (istihadhah), and abnormal bleeding (fasad blood). This condition has led to various misconceptions that may affect the proper observance of daily religious practices. This community service activity aims to improve the understanding of Indonesian migrant Muslim adolescent girls regarding the concepts, characteristics, and legal implications of menstruation, istihadhah, and fasad blood from the perspective of Islamic jurisprudence. The method employed was service learning, consisting of four stages: investigation, preparation, action, and reflection. The investigation stage was conducted through observation and interviews to identify the participants’ educational needs. Subsequently, mentoring activities were carried out through material presentation, case studies, interactive discussions, and exercises in recording menstrual cycles. The results indicated an improvement in participants’ understanding of the differences between menstruation, istihadhah, and fasad blood, as well as their understanding of the religious obligations of women experiencing istihadhah and their ability to calculate menstrual cycles more accurately. Furthermore, the participants became more confident in asking questions and more critical in selecting sources of religious information. This activity contributes to strengthening women’s fiqh literacy among Indonesian migrant Muslim adolescents and provides a contextual model of religious mentoring within non-formal educational communities.